Development of an interface based on ROS-RVIZ for calibration systems - Pina, Miguel Duarte Rocha (2021)
Sensor calibration is an essential prerequisite for many applications in the field of robotics. For complex robotic systems with several sensors of different modalities, the way to perform an extrinsic calibration is usually through sequential pairwise calibrations, which comes with its problems. The major shortcoming of sequential pairwise approaches is related to the fact that the transformation between two sensors is estimated only considering the error between the data from the selected pair of sensors. This leads to a lack of accuracy in the calibration procedure, given that, despite the fact that the pose of each sensor in relation to the other is well estimated, their pose relatively to the rest of the sensors and the robot is compromised. ATOM is a calibration framework for multi-sensor, multi-modal robotic systems, based on the optimization of atomic transformations, that offers a solution for this problems and it is integrated with the ROS framework. However, like most calibration systems, it lacks a graphical interface to facilitate the execution of the several steps of the calibration procedure. This dissertation’s goal was to create that interface and have it integrated with the ROS 3D visualization tool, RViz, as a plugin. This interface allows its users to interact with the ATOM calibration system in a more dynamic way, through graphical icons and visual indicators. Some calibrations using the developed interface were then conducted for different robotic systems to test its usability, with satisfying results, offering a more user-friendly experience for the calibration procedure.